Online learning satisfaction and its associated factors among international students in China - Tian, Mei; Lu, Genshu (Frontiers in Psychology, 2022)
The outbreak of the COVID-19 pandemic has caused a substantial transition of Chinese international education to online learning. This article discusses the impact of online learning from international students’ perspectives. Data were collected from exploratory interviews with a small group of international students at a research university and a nationwide survey involving 1,010 international students at 41 universities in China. A synthesis of the two studies’ findings pointed to low levels of online learning satisfaction, particularly among international students from Africa, those in undergraduate programs, those in life sciences and medical disciplines, and those studying at research-centered universities. Moreover, both studies revealed low emotional engagement significantly predicted international students’ online learning dissatisfaction. To enhance international students’ satisfaction, it is suggested that universities and teachers prioritize the building of student-centered online learning environments supporting international students’ emotional involvement and helping them feel a greater sense of belonging in online intercultural learning.